Influence of Circumferential Spans of Heat Flux Distributions on Secondary Flow, Heat Transfer and Friction Factors for a Linear Focusing Solar Collector Type Absorber Tube - Dirker, Jaco (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.